Probiotic Limosilactobacillus reuteri KUB-AC5 decreases urothelial cell invasion and enhances macrophage killing of uropathogenic Escherichia coli in vitro study - Tantibhadrasapa, Arishabhas; Li, Songbo; Buddhasiri, Songphon; Sukjoi, Chutikarn; Mongkolkarvin, Panupon; Boonpan, Pattarapon; Wongpalee, Somsakul Pop; Paenkaew, Prasobsook; Sutheeworapong, Sawannee; Nakphaichit, Massalin; Nitisinprasert, Sunee; Hsieh, Michael H.; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionBacterial urinary tract infections (UTI) are among the most common infectious diseases worldwide. The rise of multidrug-resistant (MDR) uropathogenic Escherichia coli (UPEC) UTI cases is a significant threat to healthcare systems. Several probiotic bacteria have been proposed as an alternative to combat MDR UTI. Lactic acid bacteria in the genus Limosilactobacillus are some of the most studied and used probiotics. However, strain-specific effects play a critical role in probiotic properties. L. reuteri KUB-AC5 (AC5), isolated from the chicken gut, confers antimicrobial and immunobiotic effects against some human pathogens. However, the antibacterial and immune modulatory effects of AC5 on UPEC have never been explored.MethodsHere, we investigated both the direct and indirect effects of AC5 against UPEC isolates (UTI89, CFT073, and clinical MDR UPEC AT31) in vitro. Using a spot-on lawn, agar-well diffusion, and competitive growth assays, we found that viable AC5 cells and cell-free components of this probiotic significantly reduced the UPEC growth of all strains tested. The human bladder epithelial cell line UM-UC-3 was used to assess the adhesion and pathogen-attachment inhibition properties of AC5 on UPEC.Results and discussionOur data showed that AC5 can attach to UM-UC-3 and decrease UPEC attachment in a dose-dependent manner. Pretreatment of UPEC-infected murine macrophage RAW264.7 cells with viable AC5 (multiplicity of infection, MOI = 1) for 24 hours enhanced macrophage-killing activity and increased proinflammatory (Nos2, Il6, and Tnfa) and anti-inflammatory (Il10) gene expression. These findings indicate the gut-derived AC5 probiotic could be a potential urogenital probiotic against MDR UTI.